Wear-resistant flame-retardant conveying belt and preparation method thereof

By using the formula of specific components in the conveyor belt cover glue, the problem of insufficient wear resistance of existing flame retardant conveyor belts is solved, and a conveyor belt with high flame retardancy and high wear resistance is achieved, meeting the needs of long-term and high-load transportation and extending its service life.

CN119613833APending Publication Date: 2025-03-14BAODING HUAYUE RUBBER BELTS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411951227.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing flame retardant conveyor belts have shortcomings in wear resistance, which is difficult to meet the long-term and high-load material transportation needs.

Method used

A wear-resistant flame-retardant conveyor belt cover is adopted, and its formula includes components such as ethylene propylene ternary rubber, styrene butadiene rubber, chlorosulfonated polyethylene rubber, Chinese super wear-resistant carbon black, white carbon black, chlorinated paraffin, nano-activated zinc oxide, modified expandable graphite and modified silicon nitride. Through the coordinated cooperation of these components, the flame retardancy and wear resistance of the material are significantly improved.

Benefits of technology

It realizes the high flame retardancy and wear resistance of the conveyor belt, the oxygen index can reach more than 60%, and the relative volume wear can be reduced to less than 50mm3, meeting the use needs under harsh working conditions, and extending the service life of the conveyor belt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214921050000171
    Figure BDA0005214921050000171
  • Figure BDA0005214921050000181
    Figure BDA0005214921050000181
Patent Text Reader

Abstract

The invention discloses a wear-resistant flame-retardant conveying belt and a preparation method thereof, and belongs to the technical field of conveying belts. The wear-resistant and flame-retardant conveying belt uses wear-resistant and flame-retardant conveying belt covering rubber as covering rubber. The wear-resistant flame-retardant conveyor belt cover rubber is prepared from the following raw materials: 20 to 30 parts of ethylene propylene diene monomer, 30 to 40 parts of butadiene styrene rubber, 30 to 40 parts of chlorosulfonated polyethylene rubber, 20 to 30 parts of medium super wear-resistant carbon black, 30 to 40 parts of white carbon black, 15 to 20 parts of chlorinated paraffin, 3 to 5 parts of nano activated zinc oxide, 2 to 6 parts of dispersing agent, 1 to 3 parts of sulfur, 2 to 6 parts of accelerant, 2 to 4 parts of anti-aging agent, 5 to 8 parts of microcrystalline wax and 2 to 3 parts of stearic acid. 15-20 parts of modified expandable graphite, 10-15 parts of modified silicon nitride and 10-15 parts of a fluorine-containing polymer. The components are synergistically matched, so that the covering rubber has excellent wear resistance and flame retardancy, and the conveyor belt prepared from the covering rubber has excellent wear resistance and flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conveyor belts, and in particular to a wear-resistant and flame-retardant conveyor belt and a preparation method thereof. Background Art

[0002] In modern industrial production, conveyor belts are an important means of material transportation, and their safety and stability are crucial to the smooth progress of the production process. Although traditional conveyor belts perform well in conventional material transportation, their insufficient fire resistance is increasingly prominent in specific environments, such as coal mines, chemicals, electricity and other flammable and explosive industrial environments. Therefore, it is particularly important to develop conveyor belts with flame retardant properties.

[0003] Flame-retardant conveyor belts are made of special flame-retardant materials, which can quickly block the spread of fire when encountering open flames or high temperatures, effectively preventing fire accidents. This feature makes flame-retardant conveyor belts have broad application prospects in the above-mentioned industrial environments. However, although the flame-retardant conveyor belts on the market have improved in flame retardancy, they are still insufficient in wear resistance and cannot meet the needs of long-term, high-load material transportation. Therefore, it is necessary to develop a conveyor belt with both excellent flame retardancy and excellent wear resistance. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant and flame-retardant conveyor belt and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a wear-resistant and flame-retardant conveyor belt covering rubber, the raw materials of which include, by weight: 20-30 parts of EPDM rubber, 30-40 parts of styrene-butadiene rubber, 30-40 parts of chlorosulfonated polyethylene rubber, 20-30 parts of medium-super wear-resistant carbon black, 30-40 parts of white carbon black, 15-20 parts of chlorinated paraffin, 3-5 parts of nano-active zinc oxide, 2-6 parts of dispersant, 1-3 parts of sulfur, 2-6 parts of accelerator, 2-4 parts of antioxidant, 5-8 parts of microcrystalline wax, 2-3 parts of stearic acid, 15-20 parts of modified expandable graphite, 10-15 parts of modified silicon nitride and 10-15 parts of fluorine-containing polymer.

[0007] In the covering rubber formula system of the present invention, chlorosulfonated polyethylene rubber and styrene-butadiene rubber are both rubbers with high wear resistance and flame retardancy, and EPDM rubber also has high thermal stability and wear resistance. The combination of the three lays the foundation for the high wear resistance and high flame retardancy of the covering rubber. The high specific surface area and unique particle morphology of super wear-resistant carbon black and white carbon black as reinforcing fillers can effectively increase the physical crosslinking points between rubber molecular chains, forming a denser network structure, thereby improving the hardness and wear resistance of the covering rubber. The modified expandable graphite expands rapidly when heated to form a multi-layer graphite sheet structure, which can effectively isolate oxygen and reflect heat to slow down the combustion rate; the modified silicon nitride can maintain structural stability at high temperatures due to its high melting point characteristics and prevent the spread of flames; the combination of the two forms a multi-level flame retardant barrier, which significantly improves the flame retardancy of the material; and both expandable graphite and silicon nitride have excellent wear resistance. The addition of the two can effectively improve the flame retardancy of the covering rubber while also effectively improving its wear resistance. The strong electronegativity of fluorine, high CF bond energy and small van der Waals radius give fluorinated polymers good thermal stability and chemical inertness, which makes fluorinated polymers perform well in high temperature and complex environments. Moreover, the fluorine element in fluorinated compounds can inhibit or slow down the spread of combustion by forming a layer of fluoride film with barrier effect under high temperature conditions, so the addition of fluorinated polymers can effectively improve the flame retardant properties of the covering rubber. Chlorinated paraffin also has excellent flame retardant properties, and its addition can further improve the flame retardant properties of the covering rubber. The above components work together to obtain a conveyor belt covering rubber with both high flame retardancy and high wear resistance.

[0008] Furthermore, the preparation method of the modified expandable graphite comprises: adding ammonia water to an aluminum nitrate solution to adjust the pH of the solution to 8-9, then adding expandable graphite, stirring evenly to obtain a precursor solution; reacting the precursor solution at a temperature of 260-360° C. for 5-8 hours to obtain the modified expandable graphite.

[0009] Through the above modification process, an AlOOH coating layer is formed on the surface of expandable graphite to obtain modified expandable graphite. When the modified expandable graphite is heated, the AlOOH coating layer that absorbs a large amount of heat decomposes to produce water vapor and aluminum oxide. The water vapor will reduce the concentration of combustible gas and the temperature of the surface of the covering rubber, and the aluminum oxide produced by the decomposition will strengthen the worm-like expanded carbon layer, increase the rigidity of the carbon layer, and make the carbon layer tightly cover the surface of the covering rubber, achieving the effect of heat insulation and oxygen isolation, greatly improving the flame retardant efficiency; and the aluminum oxide itself has excellent high temperature resistance, which is equivalent to forming another protective layer on the surface of the covering rubber, which is conducive to further improving the safety of the covering rubber.

[0010] Furthermore, the concentration of the aluminum nitrate solution is 0.2-0.3 mol / L; the concentration of the ammonia water is 10-25 wt%; and the amount of expandable graphite added is 40-60 g / L.

[0011] Furthermore, the preparation method of the modified silicon nitride includes: mixing silicon nitride, a silane coupling agent and water, stirring and reacting at a temperature of 50-60°C for 4-6 hours to obtain preliminary modified silicon nitride; mixing the preliminary modified silicon nitride with sodium phytate and chitosan solution, stirring and reacting at a temperature of 70-80°C for 1-3 hours, adding nickel acetate, and continuing to stir and react for 2-4 hours to obtain the modified silicon nitride.

[0012] Through the above modification process, the silane coupling agent is used to graft the intumescent flame retardant chitosan and nickel phytate (sodium phytate reacts with nickel acetate to form nickel phytate) on the surface of silicon nitride. Both chitosan and nickel phytate have excellent flame retardant properties, and the introduced nickel ions can also serve as a catalyst for the dehydrogenation reaction, which can improve the crosslinking degree and thermal stability of the intumescent flame retardant chitosan at high temperatures, which helps to improve the carbon formation ability and achieve better flame retardant effect.

[0013] Furthermore, the chitosan solution is prepared by dissolving chitosan in a 1 wt % acetic acid aqueous solution to obtain a chitosan solution with a chitosan solubility of 1 wt %.

[0014] Furthermore, the usage ratio of the silicon nitride, silane coupling agent and water is 10g:1-3g:600-800mL; the usage ratio of the preliminary modified silicon nitride to sodium phytate, chitosan solution and nickel acetate is 1g:1-2g:120-150mL:1-2g.

[0015] Furthermore, the silane coupling agent is KH560.

[0016] Furthermore, the preparation method of the fluorine-containing polymer includes: mixing perfluoroalkyl ethyl acrylate, glycidyl methacrylate, an emulsifier and water, heating to 30-40°C and stirring for emulsification for 30-40 minutes, then heating to 70-80°C, adding an initiator and polymerizing for 3-5 hours to obtain the fluorine-containing polymer.

[0017] The fluorinated polymer obtained by polymerization of perfluoroalkylethyl acrylate and glycidyl methacrylate as monomers contains not only a large amount of fluorine elements, but also epoxy functional groups. The introduction of epoxy functional groups in the rubber compound can change the thermal decomposition behavior of the rubber, increase the thermal decomposition temperature of the rubber, and reduce the flammable gas produced by the decomposition; the introduction of epoxy functional groups can also increase the hardness of the rubber, so that the rubber can better maintain its shape and integrity when subjected to friction.

[0018] Furthermore, the emulsifier is sodium dodecyl sulfate, the initiator is ammonium persulfate; the mass ratio of the perfluoroalkyl ethyl acrylate to glycidyl methacrylate is 1:1-2; the amount of the emulsifier is 1.5-2.5% of the sum of the mass of the perfluoroalkyl ethyl acrylate and the glycidyl methacrylate; the amount of the initiator is 0.5-1% of the sum of the mass of the perfluoroalkyl ethyl acrylate and the glycidyl methacrylate.

[0019] Furthermore, the amount of water used is 4-6 times the sum of the mass of perfluoroalkylethyl acrylate and glycidyl methacrylate.

[0020] Furthermore, after the polymerization reaction is completed, the method further comprises the steps of demulsifying with a saturated sodium chloride solution, filtering, washing and drying.

[0021] Furthermore, the dispersant is a white carbon black dispersant.

[0022] Furthermore, the accelerator is one or more of accelerator DPTT, accelerator NOBS and accelerator TMTD.

[0023] Furthermore, the antioxidant is one or more of antioxidant NBC, antioxidant 4010NA and antioxidant RD.

[0024] Technical solution 2 of the present invention: The preparation method of the above-mentioned wear-resistant and flame-retardant conveyor belt covering rubber comprises the following steps:

[0025] After the chlorosulfonated polyethylene rubber is plasticized, styrene-butadiene rubber, EPDM rubber and fluorine-containing polymer are added and mixed, then chlorinated paraffin, nano-active zinc oxide, antioxidant, microcrystalline wax, stearic acid, modified expandable graphite and modified silicon nitride are added and mixed, and finally medium-super wear-resistant carbon black, white carbon black and dispersant are added, mixed and discharged to obtain a first-stage mixed rubber;

[0026] Adding a vulcanizing agent and an accelerator to the first-stage mixed rubber, mixing for 1-2 minutes and then draining the rubber to obtain a second-stage mixed rubber;

[0027] The two-stage mixing is vulcanized to obtain the wear-resistant and flame-retardant conveyor belt covering rubber.

[0028] Furthermore, the debonding temperature of the first-stage mixed rubber is 140-150°C; the debonding temperature of the second-stage mixed rubber is 90-100°C; and the vulcanization temperature is 150-160°C.

[0029] Furthermore, the method comprises the following steps: after plasticizing the chlorosulfonated polyethylene rubber, adding butadiene styrene rubber, ethylene propylene diene monomer rubber and fluoropolymer to mix, then adding chlorinated paraffin, nano-active zinc oxide, antioxidant, microcrystalline wax, stearic acid, modified expandable graphite and modified silicon nitride to mix, and finally adding medium-super wear-resistant carbon black, white carbon black and dispersant to mix and then draining the rubber to obtain a first-stage mixed rubber, including: plasticizing the chlorosulfonated polyethylene rubber for 1-2 minutes, adding butadiene styrene rubber, ethylene propylene diene monomer rubber and fluoropolymer to mix for 2-3 minutes, then adding chlorinated paraffin, nano-active zinc oxide, antioxidant, microcrystalline wax, stearic acid, modified expandable graphite and modified silicon nitride to mix for 2-3 minutes, and finally adding medium-super wear-resistant carbon black, white carbon black and dispersant to mix for 2-3 minutes and then draining the rubber to obtain a first-stage mixed rubber; the plasticizing speed is 40-50 r / min; the mixing speed is 40-50 r / min.

[0030] Furthermore, the step of adding sulfur and an accelerator to a first-stage rubber mix, mixing and then draining the rubber to obtain a second-stage rubber mix comprises: adding sulfur and an accelerator to a first-stage rubber mix, mixing for 1-2 minutes and then draining the rubber to obtain a second-stage rubber mix; and the mixing speed is 30-40 r / min.

[0031] Furthermore, the vulcanization pressure is 10-15 MPa.

[0032] Furthermore, the vulcanization time is the positive vulcanization time measured by the vulcanization characteristic test of the corresponding two-stage mixed rubber at the corresponding temperature.

[0033] The third technical solution of the present invention: a wear-resistant and flame-retardant conveyor belt, using the above-mentioned wear-resistant and flame-retardant conveyor belt covering rubber as the covering rubber.

[0034] The present invention discloses the following technical effects:

[0035] The present invention provides a wear-resistant and flame-retardant conveyor belt covering rubber, the raw materials of which include: 20-30 parts of EPDM rubber, 30-40 parts of styrene-butadiene rubber, 30-40 parts of chlorosulfonated polyethylene rubber, 20-30 parts of medium-super wear-resistant carbon black, 30-40 parts of white carbon black, 15-20 parts of chlorinated paraffin, 3-5 parts of nano-active zinc oxide, 2-6 parts of dispersant, 1-3 parts of vulcanizing agent, 2-6 parts of accelerator, 2-4 parts of antioxidant, 5-8 parts of microcrystalline wax, 2-3 parts of stearic acid, 15-20 parts of modified expandable graphite, 10-15 parts of modified silicon nitride and 10-15 parts of fluorine-containing polymer. The above components cooperate with each other, so that the flame retardancy and wear resistance of the covering rubber are significantly improved (the oxygen index can reach more than 60%, and the relative volume wear can be reduced to 50mm 3 The covering rubber of the present invention can not only meet the use requirements of the conveyor belt under harsh working conditions, but also extend the service life of the conveyor belt and reduce the replacement frequency and maintenance cost. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0041] Conveyor belts are also called conveyor belts. They can transport various granular, powdery and piece goods. At the same time, conveyor belts also have the function of transmitting gravity during transportation. They are one of the main components of belt conveyors. Compared with other means of transportation, conveyor belts have significant advantages, such as simple material transportation and high efficiency. In addition, the formula can be adjusted according to different working conditions to meet the requirements. Therefore, conveyor belts are widely used in agriculture, industry, transportation, and especially in industrial and mining enterprises.

[0042] Conveyor belts are multi-layer, multi-material composite materials, mainly composed of base rubber and reinforcement layer skeleton materials. Generally, they include three major parts: covering rubber, core rubber / taping rubber, and skeleton material. Among them, the skeleton material is the main load-bearing structure of the conveyor belt, and is generally made of high-strength fiber fabrics or steel wire ropes that are impregnated or coated with an impregnation liquid with high bonding strength and then dried. The covering layer is in direct contact with the material and the external environment, so the performance requirements of the covering rubber are relatively high, and special requirements are also required in some scenarios, such as flame retardancy in mines or acid and alkali resistance in humid air.

[0043] Generally, the working conditions in the mine are relatively bad, and the environment that the cover rubber contacts is also relatively complex. Therefore, the detection of the related properties of the cover rubber is relatively demanding, especially the need for excellent flame retardant properties. According to the survey, it is very easy to cause fires in coal mines, and most of the reasons are caused by the poor flame retardant properties of the conveyor belt cover. Studies have shown that the main reasons for the easy occurrence of fires in mines are the following two points: the first point is that sometimes the belt is stuck during the conveying process, causing the conveyor belt to not move while the roller is always rotating. The friction between them inevitably generates high temperature, causing the belt with poor flame retardancy to burn, or generating sparks that reach the ignition point of the coal, which is extremely harmful. The second point is that due to the complex environment in the coal mine, cables, transformers and other related electrical equipment that have not been replaced for a long time are very easy to catch fire. When the fire source approaches the flammable conveyor belt, the fire will spread rapidly, causing personal injury.

[0044] The combustion of conveyor belt rubber can be divided into three stages. The first stage: the cover layer is decomposed by heat; when the conveyor belt cover layer contacts the external heat source or generates heat by its own friction, the rubber begins to soften. As the temperature continues to rise, the cover layer rubber decomposes and produces various small molecular substances, such as combustible gas carbon and hydrogen and residual carbon solid particles, which are mainly related to the composition of the cover rubber. The second stage: combustion; decomposition generates a large number of small molecular flammable substances and combustible gases, which will come into contact with the air and react violently. In the process of reaction, a large amount of heat will also be released to further increase the external temperature, thereby causing the rubber to burn. The third stage: continued combustion; the rubber continuously releases heat during the combustion process. When there is sufficient oxygen, it will continue to decompose and burn, and the combustion process will continue to spread.

[0045] According to the analysis of conveyor belt rubber combustion, it is known that rubber combustion is generally divided into three stages. In the process of studying rubber flame retardancy, the main focus is on isolating any one or more combustion processes. For this reason, some researchers have proposed that in the process of preparing conveyor belts, rubber that does not contain carbon elements and other flammable substances on the main chain should be selected as the matrix of the covering rubber. Silicone rubber is commonly used now. At the same time, some researchers have proposed another solution, which is to add an appropriate amount of flame retardant to the system to inhibit the combustion of rubber through the flame retardant effect of the flame retardant. The method we often use is to add appropriate flame retardants, and the mechanism of action of flame retardants includes: (1) Inhibition effect. Flame retardants can react with hydroxyl groups to generate water, thereby cutting off the reaction chain of free radicals, inhibiting the occurrence of oxidation reactions, and cutting off free radical reactions to achieve a good flame retardant effect. (2) Isolating oxygen or preventing heat transfer. For example, zinc borate will decompose under high temperature conditions, so that a protective layer is covered on the surface of the conveyor belt. (3) Decomposition during the combustion process generates a large amount of heat-absorbing components to prevent combustion. For example, zinc borate can decompose bound water to absorb system heat. In addition, in engineering applications, more options are to use multiple flame retardants synergistically, which have more effective flame retardant properties, such as halogen-antimony.

[0046] At present, PVC and PVG whole-core flame-retardant conveyor belts developed at home and abroad are mostly used in coal mines. The covering layer materials of PVC and PVG whole-core flame-retardant conveyor belts use PVC and PVC / rubber as the matrix, and the composite materials are prepared by the traditional halogen-antimony flame retardant system to achieve a balance between flame retardant properties and mechanical properties and processing properties. The skeleton material is a whole-core fabric skeleton material. At present, the weft and warp of the overall belt core are mainly polyester / cotton yarn or nylon / cotton yarn, so the belt body is thick, heavy, low in strength, poor in wear resistance, and short in service life. The conveyor belt field has not yet broken through the key technical bottleneck of balancing the excellent flame retardant properties of the covering rubber with the mechanical properties (especially wear resistance) and processing properties, and there are still few conveyor belt products with both high flame retardancy and high wear resistance.

[0047] The existing flame-retardant conveyor belts are mainly made of polyvinyl chloride (PVC) as the main covering material, PVG as the main covering material or chloroprene rubber (CR) as the main covering material. The structural formula of polyvinyl chloride (PVC) is CH2=CHCl, and the molecular chain contains chlorine elements. Generally, the chlorine content is above 57%, and the oxygen index (LOI) is above 45%. When polyvinyl chloride is burned and heated, it releases chlorine free radicals, which react with the flammable and active hydroxyl groups generated by the combustion of polyvinyl chloride to terminate the continued combustion of polyvinyl chloride and play a flame retardant role. Therefore, polyvinyl chloride (PVC) was first used as the main material for the covering layer to make it have flame retardant properties. When PVC is used as the main material, in order to meet the elasticity and processing performance of the conveyor belt, a large amount of plasticizers and other fillers need to be added to PVC. In this case, the chlorine content in PVC drops significantly, weakening the flame retardant properties of PVC itself. Therefore, it is necessary to add certain flame retardant synergists or flame retardants to improve the flame retardant properties of PVC. Antimony trioxide is the most commonly used flame retardant additive in PVC. Polyvinyl chloride and other chlorinated polymers have a long history of use as the main material of the covering rubber in flame-retardant conveyor belts. In the early stage of a fire, antimony trioxide itself is inert because its sublimation temperature is 1550°C. There are many studies on the flame retardant effect of antimony trioxide and chlorinated polymers, and many scholars have discovered new antimony complexes. Cullis CF believes that although some chlorine oxides can volatilize into the flame, antimony trichloride (antimony trichloride, boiling point 223°C) generated by a series of reactions between PVC and antimony trioxide is the main contributor in the reaction of clearing and suppressing flames. The oxygen index (LOI) of PVC increases almost linearly with the increase of antimony trioxide concentration. In addition to antimony trioxide, other antimony-containing complexes such as antimony pentoxide also play an important role when added to PVC materials. For example, Niranjan Karak and Sukumar Maiti studied the effects of antimony-containing polymer AP and antimony trioxide on the flame retardant properties of PVC / DOP materials with different ratios. It was found that when Sb / Cl increased, the LOI of PVC materials with different ratios continued to increase. When Sb / Cl reached 0.03, the material LOI reached the maximum. Therefore, the traditional covering layer material with PVC as the main body also adopted antimony-chlorine and ATH system. However, the traditional PVC covering rubber material formula has imperfect ratios and dosages between flame retardants, and the flame retardant synergy is not obvious, resulting in an increase in the amount of flame retardants, an increase in the cost of covering rubber materials, and poor wear resistance.

[0048] PVC covering material has high strength and good flame retardant performance, but its toughness, softness and elasticity are still inferior to rubber materials. The conveyor belt is prone to slipping and deviation during the conveying of materials, and the flexibility and wear resistance of the conveyor belt are poor. Therefore, many scholars at home and abroad have studied adding NBR (nitrile rubber) to PVC to improve the elasticity and wear resistance of the covering material. Huang Zhaoge successfully developed a flame retardant PVG covering rubber material that meets the requirements of the national standard MT914-2002. Its main material is PVC / P 83 (goodyear powdered nitrile rubber) (70 / 30), at the same time, the study found that with the P 83 In the range of 0-40phr, the tensile strength of the covering rubber decreased from 19MPa to 16MPa, the tear strength decreased from 80kN / m to 45kN / m, the oxygen index decreased from 36% to 30%, the flame retardancy, tensile and tear properties decreased, but the hardness decreased from 93 to 85, the elasticity increased, and the surface resistance increased from 7×10 8 Ω is reduced to 3×10 8 Ω, antistatic performance is improved. Although its strength and toughness are improved, the performance is better, and the flame retardant performance is also excellent, it is still not possible to make the covering material have both high flame retardancy and high wear resistance.

[0049] PVG covering material solves the shortcomings of PVC materials such as elasticity and wear resistance, but it is still not as good as pure rubber materials. CR contains halogen, has good flame retardant properties and high tensile strength. Therefore, domestic and foreign scholars first studied pure rubber covering materials with CR (chloroprene rubber) as the main material. Qu Chengdong has developed a flame retardant CR / BR covering rubber material with a performance of MT 668, a tensile strength of 17MPa, an average alcohol torch flame duration of 1s, and a wear loss of 96mm. 3 , elongation at break is 600%. The optimized formula of covering rubber is: CR / BR (80 / 20), CPE (8phr), N330 (30phr), plasticizer: phosphate ester (5phr), flame retardant (40phr): antimony trioxide, chlorinated paraffin, zinc borate (ZB), aluminum hydroxide (ATH), MB-202 (15phr).

[0050] In summary, although the existing rubber system can achieve relatively excellent flame retardant properties, there is still a lot of room for improvement in terms of flame retardant properties alone, and it is difficult to achieve excellent wear resistance while achieving excellent flame retardant properties. Therefore, it is very necessary to develop a new rubber system to further improve the flame retardant properties of the conveyor belt covering rubber while effectively improving its wear resistance.

[0051] The first aspect of the present invention provides a wear-resistant and flame-retardant conveyor belt covering rubber. The raw materials include, by weight: 20-30 parts of EPDM rubber, 30-40 parts of styrene-butadiene rubber, 30-40 parts of chlorosulfonated polyethylene rubber, 20-30 parts of medium-super wear-resistant carbon black, 30-40 parts of white carbon black, 15-20 parts of chlorinated paraffin, 3-5 parts of nano-active zinc oxide, 2-6 parts of dispersant, 1-3 parts of vulcanizing agent, 2-6 parts of accelerator, 2-4 parts of antioxidant, 5-8 parts of microcrystalline wax, 2-3 parts of stearic acid, 15-20 parts of modified expandable graphite, 10-15 parts of modified silicon nitride and 10-15 parts of fluorine-containing polymer.

[0052] As an embodiment of the present invention, the preparation method of the modified expandable graphite includes: adding ammonia water to an aluminum nitrate solution to adjust the pH of the solution to 8-9, then adding expandable graphite, stirring evenly to obtain a precursor solution; reacting the precursor solution at a temperature of 260-360°C for 5-8h to obtain the modified expandable graphite.

[0053] As a preferred embodiment of the present invention, the concentration of the aluminum nitrate solution is 0.2-0.3 mol / L; the concentration of the ammonia water is 10-25 wt%; and the amount of expandable graphite added is 40-60 g / L.

[0054] As an embodiment of the present invention, the preparation method of the modified silicon nitride includes: mixing silicon nitride, a silane coupling agent and water, stirring and reacting at a temperature of 50-60°C for 4-6 hours to obtain preliminary modified silicon nitride; mixing the preliminary modified silicon nitride with sodium phytate and chitosan solution, stirring and reacting at a temperature of 70-80°C for 1-3 hours, adding nickel acetate, and continuing to stir and react for 2-4 hours to obtain the modified silicon nitride.

[0055] As a preferred embodiment of the present invention, the method for preparing the chitosan solution is: dissolving chitosan in a 1 wt % acetic acid aqueous solution to obtain a chitosan solution with a chitosan solubility of 1 wt %.

[0056] As a preferred embodiment of the present invention, the usage ratio of the silicon nitride, silane coupling agent and water is 10g:1-3g:600-800mL; the usage ratio of the preliminary modified silicon nitride to sodium phytate, water and nickel acetate is 1g:1-2g:120-150mL:1-2g.

[0057] As a preferred embodiment of the present invention, the silane coupling agent is KH560.

[0058] As an embodiment of the present invention, the preparation method of the fluorine-containing polymer includes: mixing perfluoroalkyl ethyl acrylate, glycidyl methacrylate, an emulsifier and water, heating to 30-40°C and stirring for emulsification for 30-40 minutes, then heating to 70-80°C, adding an initiator and polymerizing for 3-5 hours to obtain the fluorine-containing polymer.

[0059] As a preferred embodiment of the present invention, the emulsifier is sodium dodecyl sulfate, the initiator is ammonium persulfate; the mass ratio of the perfluoroalkyl ethyl acrylate to the glycidyl methacrylate is 1:1-2; the amount of the emulsifier is 1.5-2.5% of the sum of the mass of the perfluoroalkyl ethyl acrylate and the glycidyl methacrylate; the amount of the initiator is 0.5-1% of the sum of the mass of the perfluoroalkyl ethyl acrylate and the glycidyl methacrylate.

[0060] As a preferred embodiment of the present invention, the amount of water used is 4-6 times the sum of the masses of perfluoroalkylethyl acrylate and glycidyl methacrylate.

[0061] As a preferred embodiment of the present invention, after the polymerization reaction is completed, the steps of demulsification with a saturated sodium chloride solution, suction filtration, washing and drying are also included.

[0062] As a preferred embodiment of the present invention, the dispersant is a white carbon black dispersant.

[0063] As a preferred embodiment of the present invention, the accelerator is one or more of accelerator DPTT, accelerator NOBS and accelerator TMTD.

[0064] As a preferred embodiment of the present invention, the antioxidant is one or more of antioxidant NBC, antioxidant 4010NA and antioxidant RD.

[0065] The second aspect of the present invention provides a method for preparing the above-mentioned wear-resistant and flame-retardant conveyor belt covering rubber, comprising the following steps:

[0066] After chlorosulfonated polyethylene rubber is plasticized for 1-2 minutes (rotation speed is 40-50r / min), styrene-butadiene rubber, EPDM rubber and fluorine-containing polymer are added and mixed for 2-3 minutes (rotation speed is 40-50r / min), then chlorinated paraffin, nano-active zinc oxide, antioxidant, microcrystalline wax, stearic acid, modified expandable graphite and modified silicon nitride are added and mixed for 2-3 minutes (rotation speed is 40-50r / min), and finally medium-super wear-resistant carbon black, white carbon black and dispersant are added and mixed for 2-3 minutes (rotation speed is 40-50r / min) and then discharged to obtain a first-stage mixed rubber;

[0067] Adding sulfur and accelerator to the first-stage mixed rubber, mixing for 1-2 minutes (rotating speed of 30-40 r / min), and then draining the rubber to obtain a second-stage mixed rubber;

[0068] The two-stage mixing is vulcanized to obtain the wear-resistant and flame-retardant conveyor belt covering rubber.

[0069] As a preferred embodiment of the present invention, the discharge temperature of the first-stage mixed rubber is 140-150°C; the discharge temperature of the second-stage mixed rubber is 90-100°C; and the vulcanization temperature is 150-160°C.

[0070] As a preferred embodiment of the present invention, the vulcanization pressure is 10-15 MPa.

[0071] As a preferred embodiment of the present invention, the vulcanization time is the positive vulcanization time measured by the vulcanization characteristic test of the corresponding two-stage rubber mix at the corresponding temperature.

[0072] A third aspect of the present invention provides a wear-resistant and flame-retardant conveyor belt, using the above-mentioned wear-resistant and flame-retardant conveyor belt covering rubber as the covering rubber.

[0073] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0074] The raw materials used in the following examples and comparative examples (except modified graphite, modified silicon nitride and fluoropolymer) are all common commercial products, wherein the model of chlorosulfonated polyethylene rubber is CSM40, the model of styrene-butadiene rubber is SBR 1502, the trade mark of ethylene propylene diene rubber is EPDM 4570, the model of medium-super wear-resistant carbon black is N220, the model of white carbon black is L-300, the model of chlorinated paraffin is chlorinated paraffin-42, the model of nano-active zinc oxide is CY-J30, the dispersant is white carbon black dispersant XT280, the model of expandable graphite is CX-200 (200 represents mesh number), the model of silicon nitride is YQ-S31D, and the deacetylation degree of chitosan is ≥95%.

[0075] The preparation method of the modified graphite used in the following examples and comparative examples is as follows: add ammonia water (concentration of 25wt%) dropwise while stirring to a 0.25mol / L Al(NO3)3 aqueous solution to adjust the pH value of the solution to 8, then add expandable graphite (the amount of expandable graphite added is 50g / L), stir evenly, and obtain a precursor solution; keep the precursor solution at a temperature of 300°C for reaction for 6h, filter, wash, and dry after the reaction to obtain modified graphite.

[0076] The preparation method of the modified silicon nitride used in the following examples and comparative examples is as follows: silicon nitride, KH560 and water are mixed in a dosage ratio of 10g:1.5g:800mL, stirred and reacted at a temperature of 60°C for 5h, filtered, washed and dried after the reaction to obtain preliminary modified silicon nitride; preliminary modified silicon nitride, sodium phytate and chitosan solution (chitosan is dissolved in a 1wt% acetic acid aqueous solution to obtain a chitosan solution with a chitosan solubility of 1wt%) are mixed in a dosage ratio of 1g:1.5g:150mL, stirred and reacted at a temperature of 80°C for 2h, and then nickel acetate of the same mass as sodium phytate is added, and the stirring reaction is continued at a temperature of 80°C for 3h. After the reaction is completed, filtered, washed and dried to obtain modified silicon nitride.

[0077] The preparation method of the fluorine-containing polymer used in the following examples and comparative examples is as follows: under nitrogen protection, perfluoroalkyl ethyl acrylate, glycidyl methacrylate, sodium dodecyl sulfate and water are mixed in a four-necked flask (the mass ratio of perfluoroalkyl ethyl acrylate and glycidyl methacrylate is 1:1.5, the amount of sodium dodecyl sulfate is 2% of the sum of the mass of perfluoroalkyl ethyl acrylate and glycidyl methacrylate, and the amount of water is 5 times the sum of the mass of perfluoroalkyl ethyl acrylate and glycidyl methacrylate), the temperature is raised to 40°C, stirred and emulsified for 30 minutes, and then the temperature is raised to 80°C, ammonium persulfate is added (the amount of ammonium persulfate is 0.8% of the sum of the mass of perfluoroalkyl ethyl acrylate and glycidyl methacrylate) and the polymerization reaction is carried out for 5 hours. After the polymerization reaction is completed, the emulsification is broken with a saturated sodium chloride solution, the filter is suction filtered, washed with 80°C distilled water 3 times, washed with anhydrous ethanol 5 times, and vacuum dried at 50°C for 24 hours to obtain a fluorine-containing polymer.

[0078] Example 1

[0079] A wear-resistant and flame-retardant conveyor belt covering rubber, the raw materials of which are, by weight: 20 parts of EPDM rubber, 30 parts of styrene-butadiene rubber, 30 parts of chlorosulfonated polyethylene rubber, 20 parts of medium-super wear-resistant carbon black, 30 parts of white carbon black, 15 parts of chlorinated paraffin, 3 parts of nano-active zinc oxide, 2 parts of dispersant, 1 part of sulfur, 2 parts of accelerator DPTT, 2 parts of antioxidant NBC, 5 parts of microcrystalline wax, 2 parts of stearic acid, 15 parts of modified expandable graphite, 10 parts of modified silicon nitride and 10 parts of fluorine-containing polymer.

[0080] The preparation method of the wear-resistant and flame-retardant conveyor belt covering rubber comprises the following steps:

[0081] After chlorosulfonated polyethylene rubber is plasticized for 2 minutes (speed is 45r / min), styrene-butadiene rubber, EPDM rubber and fluorine-containing polymer are added and mixed for 3 minutes (speed is 45r / min), then chlorinated paraffin, nano-active zinc oxide, antioxidant, microcrystalline wax, stearic acid, modified expandable graphite and modified silicon nitride are added and mixed for 3 minutes (speed is 45r / min), and finally medium-super wear-resistant carbon black, white carbon black and dispersant are added and mixed for 3 minutes (speed is 45r / min) and then discharged (control the discharge temperature to be 140-150°C) to obtain a first-stage mixed rubber;

[0082] Add sulfur and accelerator to the first-stage mixed rubber, mix for 2 minutes (speed is 35r / min), and then discharge the rubber (control the discharge temperature at 90-100°C) to obtain the second-stage mixed rubber;

[0083] The two-stage mixed rubber is calendered on a calender to obtain a mixed rubber sheet of a certain size (the size of the mixed rubber sheet is determined according to the size of the vulcanizer and the thickness of the cover rubber to be obtained), and then vulcanized on the vulcanizer (the vulcanization temperature is 150°C, the pressure is 15MPa, and the time is the positive vulcanization time measured by the vulcanization property test of the two-stage mixed rubber at the corresponding temperature) to obtain a wear-resistant and flame-retardant conveyor belt cover rubber.

[0084] Example 2

[0085] A wear-resistant and flame-retardant conveyor belt covering rubber, the raw materials of which are, by weight: 25 parts of EPDM rubber, 35 parts of styrene-butadiene rubber, 35 parts of chlorosulfonated polyethylene rubber, 25 parts of medium-super wear-resistant carbon black, 35 parts of white carbon black, 18 parts of chlorinated paraffin, 4 parts of nano-active zinc oxide, 4 parts of dispersant, 2 parts of sulfur, 4 parts of accelerator NOBS, 3 parts of antioxidant 4010NA, 6 parts of microcrystalline wax, 3 parts of stearic acid, 18 parts of modified expandable graphite, 12 parts of modified silicon nitride and 12 parts of fluorine-containing polymer.

[0086] The preparation method of the wear-resistant and flame-retardant conveyor belt covering rubber is the same as that in Example 1.

[0087] Example 3

[0088] A wear-resistant and flame-retardant conveyor belt covering rubber, the raw materials of which are, by weight: 30 parts of EPDM rubber, 40 parts of styrene-butadiene rubber, 40 parts of chlorosulfonated polyethylene rubber, 30 parts of medium-super wear-resistant carbon black, 40 parts of white carbon black, 20 parts of chlorinated paraffin, 5 parts of nano-active zinc oxide, 6 parts of dispersant, 3 parts of sulfur, 6 parts of accelerator TMTD, 4 parts of antioxidant RD, 8 parts of microcrystalline wax, 3 parts of stearic acid, 20 parts of modified expandable graphite, 15 parts of modified silicon nitride and 15 parts of fluorine-containing polymer.

[0089] The preparation method of the wear-resistant and flame-retardant conveyor belt covering rubber is the same as that in Example 1.

[0090] Comparative Example 1

[0091] Same as Example 1, except that the modified expandable graphite is replaced by expandable graphite of equal mass.

[0092] Comparative Example 2

[0093] The same as Example 1, except that the modified expandable graphite is replaced by an equal mass of antimony trioxide.

[0094] Comparative Example 3

[0095] Same as Example 1, except that the modified silicon nitride is replaced with silicon nitride of equal mass.

[0096] Comparative Example 4

[0097] Same as Example 1, except that the fluoropolymer is replaced by PTFE 613A X (DuPont, USA) of equal mass.

[0098] Effect Example 1

[0099] The wear-resistant and flame-retardant conveyor belt covering rubbers obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to the following performance tests (during vulcanization, a suitable mold can be selected for vulcanization according to the size of the test sample required for the test):

[0100] (1) Flame retardancy: Test the oxygen index of conveyor belt covering rubber according to standard GB / T 10707-2008 "Determination of combustion performance of rubber";

[0101] (2) Wear resistance: The relative volume wear of the conveyor belt cover rubber is tested in accordance with the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)".

[0102] The test results are shown in Table 1:

[0103] Table 1

[0104]

[0105]

[0106] As shown in Table 1, compared with Example 1, the oxygen index of Comparative Example 1 is reduced (flame retardancy is reduced), and the relative volume wear loss is increased (wear resistance is reduced), indicating that the modification of expandable graphite further improves the effect of improving the flame retardancy and wear resistance of the rubber; compared with Example 1, the oxygen index of Comparative Example 2 is reduced, and the relative volume wear loss is significantly increased. Compared with the conventional flame retardant antimony trioxide, the modified expandable graphite of the present invention not only has better flame retardancy, but also has significant advantages in wear resistance; compared with Example 1, the oxygen index of Comparative Example 3 is reduced, but the relative volume wear loss is slightly increased. This is because the expanded flame retardant chitosan and nickel phytate grafted on the surface of silicon nitride through the modification process significantly improve the flame retardant properties of silicon nitride. In Example 3, after the modified silicon nitride is replaced by the unmodified silicon nitride of the same mass, the flame retardant properties of the covering rubber decrease significantly. However, after the modified silicon nitride is replaced by the unmodified silicon nitride of the same mass, the content of silicon nitride with excellent wear resistance is increased, which improves the wear resistance of the covering rubber. Compared with Example 1, the oxygen index of Comparative Example 4 is reduced and the relative volume wear is increased, indicating that the introduction of epoxy functional groups is beneficial to improving the flame retardancy and wear resistance of the covering rubber.

[0107] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A wear-resistant and flame-retardant conveyor belt covering rubber, characterized in that: Calculated by mass, the raw materials include: 20-30 parts of EPDM rubber, 30-40 parts of styrene-butadiene rubber, 30-40 parts of chlorosulfonated polyethylene rubber, 20-30 parts of medium-super wear-resistant carbon black, 30-40 parts of white carbon black, 15-20 parts of chlorinated paraffin, 3-5 parts of nano-active zinc oxide, 2-6 parts of dispersant, 1-3 parts of sulfur, 2-6 parts of accelerator, 2-4 parts of antioxidant, 5-8 parts of microcrystalline wax, 2-3 parts of stearic acid, 15-20 parts of modified expandable graphite, 10-15 parts of modified silicon nitride and 10-15 parts of fluorine-containing polymer.

2. The wear-resistant and flame-retardant conveyor belt covering rubber according to claim 1, characterized in that: The preparation method of the modified expandable graphite comprises: adding ammonia water to an aluminum nitrate solution to adjust the pH value of the solution to 8-9, then adding expandable graphite, stirring evenly to obtain a precursor solution; reacting the precursor solution at a temperature of 260-360° C. for 5-8 hours to obtain the modified expandable graphite.

3. The wear-resistant and flame-retardant conveyor belt covering rubber according to claim 2, characterized in that: The concentration of the aluminum nitrate solution is 0.2-0.3 mol / L; the concentration of the ammonia water is 10-25 wt%; and the added amount of the expandable graphite is 40-60 g / L.

4. The wear-resistant and flame-retardant conveyor belt covering rubber according to claim 1, characterized in that: The preparation method of the modified silicon nitride comprises: mixing silicon nitride, a silane coupling agent and water, stirring and reacting at a temperature of 50-60° C. for 4-6 hours to obtain preliminary modified silicon nitride; mixing the preliminary modified silicon nitride with sodium phytate and chitosan solution, stirring and reacting at a temperature of 70-80° C. for 1-3 hours, adding nickel acetate, and continuing to stir and react for 2-4 hours to obtain the modified silicon nitride.

5. The wear-resistant and flame-retardant conveyor belt covering rubber according to claim 4, characterized in that: The usage ratio of the silicon nitride, the silane coupling agent and water is 10g:1-3g:600-800mL; the usage ratio of the preliminary modified silicon nitride, the sodium phytate, the chitosan solution and the nickel acetate is 1g:1-2g:120-150mL:1-2g.

6. The wear-resistant and flame-retardant conveyor belt covering rubber according to claim 1, characterized in that: The preparation method of the fluorine-containing polymer comprises: mixing perfluoroalkyl ethyl acrylate, glycidyl methacrylate, an emulsifier and water, heating to 30-40° C., stirring and emulsifying for 30-40 minutes, then heating to 70-80° C., adding an initiator and polymerizing for 3-5 hours to obtain the fluorine-containing polymer.

7. The wear-resistant and flame-retardant conveyor belt covering rubber according to claim 6, characterized in that: The emulsifier is sodium dodecyl sulfate, the initiator is ammonium persulfate; the mass ratio of the perfluoroalkyl ethyl acrylate to glycidyl methacrylate is 1:1-2; the amount of the emulsifier is 1.5-2.5% of the sum of the mass of the perfluoroalkyl ethyl acrylate and the glycidyl methacrylate; the amount of the initiator is 0.5-1% of the sum of the mass of the perfluoroalkyl ethyl acrylate and the glycidyl methacrylate.

8. The method for preparing the wear-resistant and flame-retardant conveyor belt covering rubber according to any one of claims 1 to 7, characterized in that: The following steps are involved: After the chlorosulfonated polyethylene rubber is plasticized, styrene-butadiene rubber, EPDM rubber and fluorine-containing polymer are added and mixed, then chlorinated paraffin, nano-active zinc oxide, antioxidant, microcrystalline wax, stearic acid, modified expandable graphite and modified silicon nitride are added and mixed, and finally medium-super wear-resistant carbon black, white carbon black and dispersant are added, mixed and discharged to obtain a first-stage mixed rubber; Adding sulfur and an accelerator to the first-stage mixed rubber, mixing and draining the rubber, and obtaining a second-stage mixed rubber; The two-stage mixing is vulcanized to obtain the wear-resistant and flame-retardant conveyor belt covering rubber.

9. The preparation method according to claim 8, characterized in that: The discharge temperature of the first-stage mixed rubber is 140-150°C; the discharge temperature of the second-stage mixed rubber is 90-100°C; and the vulcanization temperature is 150-160°C.

10. A wear-resistant and flame-retardant conveyor belt, characterized in that: The wear-resistant and flame-retardant conveyor belt covering rubber described in any one of claims 1 to 7 is used as the covering rubber.